Enabling Circular Economy: The Overlooked Role of Inorganic Materials Chemistry. Issue 22 (22nd March 2021) - Salviulo, Gabriella; Lavagnolo, Maria Cristina; Dabalà, Manuele; Bernardo, Enrico; Polimeno, Antonino; Sambi, Mauro; Bonollo, Franco; Gross, Silvia
Abstract: Circular economy is considered a new chance to build a more sustainable world from both the social and the economic point of view. In this Essay, the possible contribution of inorganic chemistry towards a smooth transition to circularity in inorganic materials design and production is discussed by adopting an interdisciplinary approach. Abstract : Circular economy, acknowledged as "an opportunity to rethink our economic future", is considered a new chance to build a more sustainable world from both the social and the economic point of view. In this Essay, the perspective contribution of inorganic chemistry towards a smooth transition to circularity in inorganic materials design and production, to enable them to enter into the circular loop, is outlined by adopting a truly interdisciplinary approach, encompassing expertise in inorganic materials chemistry, modelling, materials engineering, circular waste management, metallurgy, and mineralogy.